CFD modelling of the off-gas system of HIsarna iron making process. Part 1: model development using detailed reaction mechanism for post-combustion of CO–H2 mixture and carbon particles. (14th September 2022) - Hosseini, Ashkan; Dhiman, Vinod; Meijer, Koen; Zeilstra, Christiaan; Hage, Johannes; Peeters, Tim; Offerman, Erik; Yang, Yongxiang
ABSTRACT: The HIsarna process is a new and breakthrough smelting reduction process for hot metal (liquid iron) production from iron ores and coal directly fed into the reactor. The flue gas from the main reactor enters the off-gas system containing small amounts of H2, CO and carbon particles which need to be removed before further treatment by post combustion oxygen injection. A three-dimensional Computational Fluid Dynamics (CFD) simulation of the HIsarna off-gas system is performed and validated using a detailed reaction mechanism and kinetic data for post-combustion of a CO–H2 mixture and carbon particles. Using the validated model, a series of simulations were performed to investigate the effect of water quenching and post combustion oxygen injection. It was found that water quenching can significantly reduce the off-gas temperature. It is also possible to reduce oxygen injection during operations where inlet CO content of the off-gas system is low.